A Review On Different Methods Development Approaches Of Micro Sponge’s Drug Delivery System - Ashwini Potulwar, Sailesh J Wadher, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Microsponges delivery system is a apparent polymeric system consisting of porous microspheres. These are tiny sponge like spherical particles those consist of a myriad of interconnecting voids within a non-collapsible structure with a big porous surface through which active ingredients are released in a controlled manner. The size of the microsponges scale from 5 to 300 micrometer in diameter and a typical 25 micrometer sphere can have upto 2.5 lac pores and an internal pore structure equivalent to ten feet in length, providing a total pore volume of about 1milli litre per gram for extensive drug retention. This review gives all information regarding the methods available for preparation and development of Micro sponges